Safeguarding sloths and anteaters in the future: Priority areas for conservation under climate change. (15th December 2022) - Borges, Christielly; Bertassoni, Alessandra; Liévano‐Latorre, Luisa F.; Dória, Thaís Andrade Ferreira; Santos‐Silva, Rejane; Miranda, Flávia; Barreto, Elisa
Abstract: Sloths and anteaters form the monophyletic order Pilosa, which is currently represented by only 16 extant species distributed exclusively in the Neotropics. This present‐day low species richness is an inheritance of the Pleistocene megafaunal extinctions, where over 65 Pilosa species known from the fossil record went extinct. The large number of species lost in the recent past suggests that this group is greatly vulnerable to extinction. Here, we propose long‐term priority conservation areas for the order Pilosa, considering different future climate change scenarios, biotic stability, and the multiple dimensions of the group's biodiversity, such as species richness, species endemism, and phylogenetic diversity. Projections of species distribution for future scenarios show increased fragmentation and clear habitat loss as the Amazon Forest is replaced by savanna‐like habitats. Conservation solutions were highly congruent for the different dimensions of biodiversity, with priority areas emerging mainly in the Atlantic Forest, Amazonian wetlands, highlands of Ecuador, and the Central American isthmus. Expanding the currently protected areas network by 6% with the proposed priority areas, independently of which future climatic scenario is considered, can increase sloths and anteaters' coverage in the future by 12%. As a group of high phylogenetic and ecological importance, future conservation planning should deliberately aim to protect areas favorable to Pilosa, especially given the current scenario of environmental dismantling and neglect of critical Neotropical biomes. Abstract in Portuguese is available with online material. Abstract : Present‐day low species richness of Pilosa (16 species) is an inheritance of the Pleistocene megafaunal extinctions, suggesting that this group is greatly vulnerable to extinction. Here, we propose long‐term priority conservation areas for the order Pilosa, considering different future climate change scenarios, biotic stability, and the multiple dimensions of the group's biodiversity. Our conservation solutions were highly congruent and expanding the currently protected areas network by 6%, increases Pilosa's future coverage by 12%. Abstract: Preguiças e tamanduás formam a ordem monofilética Pilosa, que atualmente é composta por apenas 16 espécies distribuídas exclusivamente nos Neotrópicos. Essa atual baixa riqueza de espécies é uma herança das extinções da megafauna do Pleistoceno, onde mais de 65 espécies de Pilosa conhecidas pelo registro fóssil foram extintas. O elevado número de espécies extintas nesse passado recente sugere que este grupo é altamente vulnerável à extinção. Aqui propomos áreas de conservação prioritárias de longo prazo para a ordem Pilosa, considerando diferentes cenários futuros de mudanças climáticas, estabilidade biótica e as múltiplas dimensões da biodiversidade do grupo, como riqueza de espécies, endemismo de espécies e diversidade filogenética. Projeções de distribuição de espécies para cenários futuros mostram maior fragmentação e clara perda de habitat à medida que a Floresta Amazônica é substituída por habitats semelhantes a savanas. As soluções de conservação foram altamente congruentes para as diferentes dimensões da biodiversidade, com áreas prioritárias emergindo principalmente na Mata Atlântica, pântanos amazônicos, terras altas do Equador e istmo da América Central. Ampliar em 6% a rede de áreas protegidas atualmente com as áreas prioritárias propostas, independentemente de qual cenário climático futuro seja considerado, pode aumentar a cobertura de preguiças e tamanduás no futuro em até 12%. Uma vez que se trata de um grupo de alta importância filogenética e ecológica, planejamentos de conservação futuros devem deliberadamente visar a proteção de áreas favoráveis a Pilosa, especialmente diante do cenário atual de desmantelamento ambiental e negligência de biomas Neotropicais.